The earthscan atlas series, 11 vols : the atlas of war and peace - Smith, Dan. ([S.l.] : Earthscan, 2003)
At rare moments it seems a new era is starting before our eyes and history is about to change very fast. September 11, 2001 was such a moment. The latest edition of this classic reference takes us beyond the headlines. It provides a global overview of the causes and consequences of war today and the dynamics of peacemaking. It analyses current wars, their backgrounds, their trends and their prospects on every continent. From Iraq to Sierra Leone, the Middle East to Northern Ireland, Colombia to Afghanistan, The Atlas of War and Peace maps the problem of war and the challenge of peace in the 21st century. Its unique format gives shape and meaning to the statistics about the world's war zones and armed forces, and makes it an indispensable resource for understanding the world we live in.
Keywords: Military history, Modern; World politics